Synthetic Organo-Selenium Compounds in Medicinal Domain: A Review - Ahmad Akhoon, Showket; Naqvi, Tahira; Nisar, Safiya; Ahmad Rizvi, Masood (Asian Journal of Chemistry, 2015)
Organoselenium chemistry has emerged as an outstanding area in recent years due to its essential role in synthesis of a large number of biologically active compounds and important therapeutic products. The design and synthesis of organoselenium compounds with improved biological activity continues to be an active area of research. This minireview discusses the different medicinal applications of a plethora of synthetic organoselenium compounds from last two and a half decade. This mini review is aimed to be handy reference for synthetic chemists in designing and synthesizing novel organoselenium compounds of therapeutic significance.